The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fpsyt.2020.603875
|View full text |Cite
|
Sign up to set email alerts
|

Mental Distress and Human Rights Violations During COVID-19: A Rapid Review of the Evidence Informing Rights, Mental Health Needs, and Public Policy Around Vulnerable Populations

Abstract: Background: COVID-19 prevention and mitigation efforts were abrupt and challenging for most countries with the protracted lockdown straining socioeconomic activities. Marginalized groups and individuals are particularly vulnerable to adverse effects of the pandemic such as human rights abuses and violations which can lead to psychological distress. In this review, we focus on mental distress and disturbances that have emanated due to human rights restrictions and violations amidst the pandemic. We underscore h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 55 publications
2
33
0
1
Order By: Relevance
“…We included six systematic reviews with original studies on work-related stigmatization due to COVID-19 exposure in our literature search [28,30,33,[46][47][48]. Four of the reviews [28,30,33,46] only included one original study in their review, which we all iden-tified by our systematic search (original studies: Blake et al [49], Chatterjee et al [50], Juan et al [51], and Mohindra et al [38]).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…We included six systematic reviews with original studies on work-related stigmatization due to COVID-19 exposure in our literature search [28,30,33,[46][47][48]. Four of the reviews [28,30,33,46] only included one original study in their review, which we all iden-tified by our systematic search (original studies: Blake et al [49], Chatterjee et al [50], Juan et al [51], and Mohindra et al [38]).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Despite constant media awareness campaigns and efforts, many patients are faced with uncertainty and expressed some degree of psychosocial distress as a result of this pandemic [ 23 24 25 ]. In our study, we found that most of the patients were reasonably happy and accepted the current clinical arrangements under this COVID situation, although some patients expressed dissatisfaction (35.7%) and hold a pessimistic view on the current healthcare system (28.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Equally, the government of Kenya promptly implemented measures such as suspension of international ights, partial lockdown, school closure, curfew, compulsory wearing of masks, a ban on social gatherings, restriction of business operating hours, social distancing and cessation of movement across cities following a marked rise in the COVID-19 cases [7,8]. Incidentally, these restrictions to mitigate the pandemic have contributed to vulnerabilities such as strained socioeconomic activities, uncertainty, anxiety, mental distress, loss of livelihoods and violation of human rights as reported in previous studies [9,10]. Moreover, disruption of food systems has heightened food insecurity while the nancial power to access food has been affected as reported in a study conducted in Uganda and Kenya [11].…”
Section: Introductionmentioning
confidence: 87%